A pioneering and enlightening doctoral dissertation on medical education: Horsch’s German thesis (1807) - Inés Mª Fernández-Guerrero; Manuel Torralbo-Rodríguez; Cristina Fernández-Guerrero; Antonio Fernández Cano (Revista Española de Educación Médica)
Introduction. This study analyzes a German doctoral thesis entitled Über die Bildung des Arztes als Klinikers und als Staatsdieners (On the Education of Physicians as Clinicians and Civil Servants), defended by Philipp Joseph Horsch (1772-1820) at the University of Würzburg in 1807, possibly the world's first doctoral thesis in the field of medical education. Method. This study is a historiographical and bibliographic review of an academic document, a doctoral dissertation retrieved from the German LEVIVO database. Therefore, it is a documental case study. Results. The academic context and its agents are easily inferable: the University of Würzburg with its associated clinical hospital, the Julius Hospital (Juliusspital) and its medical professors. At the beginning of the 19th century, Europe was immersed in the devastating Napoleonic wars. The text addresses a series of dilemmas related to basic conceptions of medical education, established as dichotomies to be overcome by emphasizing clinical teaching. These dilemmas included: the new versus the old, theory versus practice, medicine as an art versus as a science, hospital versus outpatient medicine, and state physicians versus private ones, which the author does not consider antagonistic, or exclusive, but rather options that can be integrated, synthesized, because they are basically complementary and solvable through hybrid solutions. The author's extensive attention to physicians as civil servants is discussed. In addition, a number of pedagogical recommendations are inferred from the thesis. Discussion. The thesis offers a novel vision of medical education for its time, containing a series of considerations that are still relevant today in the movement of Practical Medicine. Throughout the thesis there are abundant educational recommendations that should not be ignored because they are perennial, in the Leibnizian sense of the term.